The psychological impact of the COVID-19 epidemic among healthcare workers at the grassroots level in Vietnam - Hoa, Nguyen Phuong; Ly, Tran Thi; Nguyet, Nguyen Thi; Thuy, Hoang Thu; Giang, Pham Ngan (Intelektual Pustaka Media Utama, 2024)
The COVID-19 pandemic has significantly affected the mental health of healthcare workers (HCWs). Therefore, an immediate priority is to monitor rates of mental health issues to understand related factors and inform interventions. The main purpose of this study was to evaluate the psychological and mental health impact of COVID-19 and some related factors among HCWs at the grassroots level in Vietnam. A cross-sectional study was conducted on 675 HCWs working at health facilities through questionnaires. The finding showed the rate of HCWs who were psychologically affected by the COVID-19 pandemic was 37.2%, of which 64.1% of HCWs were afraid to tell their families about the risk of exposure to COVID-19 at work. The 31.0% of HCWs had difficulty sleeping deeply/insomnia due to the COVID-19 epidemic. No statistically significant differences were found in the psychological impact of COVID-19 between HCW groups by age, gender, seniority, and professional qualifications. Some groups of HCWs were found to have poor psychological health. Our research suggests that during the COVID-19 pandemic, HCWs working in healthcare facilities experienced an increased psychological burden; psychological interventions for those at high risk and with common mental disorders should be included to reduce this burden and protect HCWs' mental health.